Pengembangan Website PT. Rantangin Digital Indonesia Menggunakan Framework Next Js dan Tailwind CSS - Puan Maharani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to develop the company website PT. Rantangin Digital Indonesia uses the latest technology, namely Next.js and Tailwind CSS. This website development was carried out to increase visibility and user experience in accessing the services offered by the company. Next.js was chosen as the development framework because of its ability to build fast, scalable and SEO-friendly web applications, while Tailwind CSS was used to speed up the interface design process with a flexible and responsive utility-first approach. The development method used is the Waterfall method, which consists of planning, design, implementation, testing and maintenance stages. The development results show that the website built has succeeded in fulfilling the company's goals of providing a digital platform that is easy to access, responsive on various devices, and has optimal performance. By using Next.js and Tailwind CSS, website development can be done efficiently and effectively, and provide a better user experience. Recommendations for further development include integration with content management systems and analytical features for monitoring website performance.